Ketahanan masyarakat terhadap banjir akibat hujan lebat di Kelurahan Mangkang, Kota Semarang - Kusuma Kusuma; Deffi Ayu Puspito Sari; Setyo Aji Pramono (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2026)
Mangkang Wetan Sub-district is one of the areas in Semarang City that frequently experiences flooding triggered by heavy rainfall. Data from the National Disaster Management Agency (BNPB) indicate that flooding occurred more than ten times per year in Semarang City during 2019–2022 and reoccurred in January 2023, including in Mangkang Wetan. This condition has encouraged local communities to remain and adapt to recurring flood risks. This study aims to assess the level of community resilience in Mangkang Wetan Sub-district in facing flood hazards. A mixed-method approach was employed, with data collected through questionnaires distributed to flood-affected residents. Community resilience was assessed across five dimensions: physical, social, economic, government role, and natural environment. Questionnaire data were compiled, validated, statistically analyzed, and discussed exploratively. The results show resilience scores of 1.95 for the physical dimension, 2.15 for social, 1.80 for economic, 1.95 for government role, and 1.75 for the natural dimension on a 1–3 scale. Overall, community resilience falls within the moderate (less resilient) category. The natural dimension represents the weakest aspect and requires targeted improvement. Enhancing community awareness and preparedness, particularly during rainfall events exceeding 25 mm/day, is essential to support more adaptive and resilient regional development.